Ecology and genetics affect relative invasion success of two Echium species in southern Australia - Zhu, Xiaocheng (Sci Rep, 2017)
Echium plantagineum and E. vulgare are congeneric exotics first introduced to Australia in the early 1800 s. There, E. plantagineum is now highly invasive, whereas E. vulgare has a limited distribution. Studies were conducted to evaluate distribution, ecology, genetics and secondary chemistry to shed light on factors associated with their respective invasive success. When sampled across geographically diverse locales, E. plantagineum was widespread and exhibited a small genome size (1 C = 0.34 pg), an annual life cycle, and greater genetic diversity as assessed by DNA sequence analysis. It was found frequently in areas with temperature extremes and low rainfall. In contrast, E. vulgare exhibited a larger genome size (1 C = 0.43 pg), a perennial lifecycle, less chloroplast genetic diversity, and occurred in areas with lower temperatures and higher rainfall. Twelve chloroplast haplotypes of E. plantagineum were evident and incidence aligned well with reported historical introduction events. In contrast, E. vulgare exhibited two haplotypes and was found only sporadically at higher elevations. Echium plantagineum possessed significantly higher levels of numerous pyrrolizidine alkaloids involved in plant defence. We conclude that elevated genetic diversity, tolerance to environmental stress and capacity for producing defensive secondary metabolites have contributed to the successful invasion of E. plantagineum in Australia.